2003
DOI: 10.1034/j.1601-0825.2003.02888.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially malignant oral lesions in Northern Ireland: size (extent) matters

Abstract: Of all the features considered in our series, size (extent) was the most important clinical factor in determining the risk of future SCC in PML, particularly when several adjacent anatomical sites were affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 26 publications
6
42
2
4
Order By: Relevance
“…Similar to other studies, our findings showed that lichen planus and lichenoid lesions were the most common types of OPMDs (Napier et al, 2003;Warnakulasuriya et al, 2011). Although there is controversy as to the potentially malignant nature of these conditions (Lodi et al, 2005;Van der Meij et al, 2007), it is generally accepted that lichen planus/lichenoid lesions can be OPMDs (Warnakulasuriya et al et al, 2007;Van der Waal, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Similar to other studies, our findings showed that lichen planus and lichenoid lesions were the most common types of OPMDs (Napier et al, 2003;Warnakulasuriya et al, 2011). Although there is controversy as to the potentially malignant nature of these conditions (Lodi et al, 2005;Van der Meij et al, 2007), it is generally accepted that lichen planus/lichenoid lesions can be OPMDs (Warnakulasuriya et al et al, 2007;Van der Waal, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…A treatment that is useless in nine time out of ten should be, at least, absolutely safe. Something that is not true for a number of medical treatment proposed [6], and probably for surgery, particularly for large lesions (which, by the way, are those at higher risk) [4,5,7].…”
mentioning
confidence: 99%
“…Na literatura consultada não há consenso entre os fatores de risco para os desfechos clínicos, inclusive alguns autores não observaram nenhuma associação entre os fatores e desfechos (Saito et al, 2001;Wylie, 2002;van der Hem et al, 2005). Porém, alguns fatores como paciente do gênero feminino sem hábitos de tabagismo, tamanho da lesão, e displasia epitelial intensa, são referenciados como os mais frequentemente associados aos desfechos clínicos (Schepman et al, 1998;Napier et al, 2003;Chandu;Smith, 2005;Holmstrup et al, 2006 (Warnakulasuriya, 2000;Warnakulasuriya et al, 2008). Diversos marcadores moleculares associados à transformação maligna têm sido investigados para diferentes tipos de neoplasias malignas.…”
Section: Análise Da Expressão Dos Anticorposunclassified
“…Em nações desenvolvidas, a maior parte dos indivíduos é acometida pela LO entre a 6ª e 7ª década de vida, já nos países em desenvolvimento ocorrem, em média, de 5 a 10 anos antes (Silverman et al, 1984;Lumerman et al, 1995;Jaber et al, 2003;Napier et al, 2003;Dietrich et al, 2004;Nagao et al, 2005;Speight, 2008). A taxa de transformação maligna parece não variar com a idade (Petti, 2003).…”
Section: Introductionunclassified
See 1 more Smart Citation